PENGARUH FINANCIAL KNOWLEDGE, FINANCIAL LITERACY, PARENTAL INCOME, DAN LOCUS OF CONTROL TERHADAP FINANCIAL MANAGEMENT BEHAVIOR PADA MAHASISWA DI PONDOK PESANTREN - Eka Felantika (Jurnal Ilmu Manajemen, 2022)
This research aims to determine the effect of financial knowledge, financial literacy, parental income, and locus of control on financial management behaviour for students living in an Islamic boarding school. The sampling technique used for this research is purposive sampling with a total sample of 100 respondents. The characteristics of respondents are students living in Islamic boarding schools in Ponorogo, aged 17-24 years, and still getting pocket money from their parents. The data used primary data obtained from the questionnaire. The analysis technique used by the researcher is multiple linear regression analysis and processed by SPSS 25. The results show that financial knowledge affects financial management behaviour. Financial literacy does not involve financial management behaviour because many students consider financial literacy to be necessary, but only a tiny percentage of them apply it skillfully. Parental income does not affect financial management behaviour because the source of student pocket money does not only come from parents' income. Locus of control affects financial management behaviour. From this research, students are expected to be able to demonstrate good financial management behaviour and be able to manage finances and also make good financial decisions.